HUBUNGAN WAKTU PULIH SADAR DENGAN KEJADIAN AGITASI PASCA GENERAL ANESTESI DI RSUD SLEMAN - Maulidina, Selly; Riyadi, Raden Sugeng; Listyaningrum, Tri Hapsari (Jurnal Ilmiah Kesehatan Media Husada, 2025)
Background: Surgery is one of the essential medical procedures in health services. Patients undergoing surgical procedures require anesthesia. One of the complications that often occurs after general anesthesia during recovery after using the sevoflurane agent is cases of agitation, which are caused by several factors, including the time to recover consciousness. Aim of the Study: The study aimed to determine the relationship between recovery time and cases of agitation after general anesthesia. Research Method: This type of research is quantitative research with a cross-sectional survey research design. 79 respondents were selected using purposive sampling techniques with inclusion and exclusion criteria. Data analysis was carried out using the Spearman rank test. Findings: The majority of respondents were shown to be 42 (53.2%) experiencing agitation after general anesthesia, and two respondents (2.5%) experiencing very agitation. Respondents who experienced cases of agitation with a quick recovery time were 37 respondents (46.8%). The research results show p-value = 0.000 and a correlation coefficient of 0.866. Conclusion: There is a significant relationship between the time to recover consciousness and cases of agitation after general anesthesia at Sleman Regional Hospital, with a very strong correlation, and the direction of the relationship is positive. This finding suggests that a quicker recovery time may lead to a higher incidence of post-anesthesia agitation. Suggestion: The results of this research are expected to serve as an evaluation for the Sleman District Hospital so that there are operational standards (SOP) regarding handling agitation cases after general anesthesia in the recovery room.